IMPLEMENTASI AIR OZON DALAM MENURUNKAN KOLONI BAKTERI PADA LUKA PASIEN DIABETIC FOOT ULCER - Pradika, Jaka; Pratama, Kharisma; Amrullah, Syahid (Jurnal Keperawatan dan Kesehatan, 2021)
Background: Diabetic foot ulcer (DFU) is a condition of infection, ulceration and or destruction of connective tissue caused by neuropathy, ischemic or whole (neuroiskemic). Wound Cleansing is an important initial step in cleaning the wound. Ozone water which contains bacterial activity is a suitable cleaning fluid to maximize the cleanliness of DFU. Objective: Knowing the effect of wound cleansing using Ozone Water in reducing bacterial colonies and wound healing in DFU. Methods: This study used a quasi-experimental method with pre-test post-test control group design. The total sample of 44 respondents who were divided into Ozone and NaCl were 0.9%. Each group cleansed the wound using ozone water and 0.9% NaCl. The sampling technique uses consecutive sampling and counting the number of bacteria using the Bacterial Counter tool and assessment score of wound healing used instrument of Bates Jensen Wound Assessment Tools (BJWAT). Results: The BJWAT score in the Ozone and NaCl 0.9% group had significance values (p = 0.018) and (p = 0.012). Conclusion: There was no significant difference in wound cleansing between ozone water and 0.9% NaCl in reducing the number of bacterial colonies and wound healing in DFU. Suggestion: Further research is needed with larger samples and other comparative fluids.